Reducing volatility due to natural gas exports: Is the answer a stabilization fund? - Lykke E. Andersen; Robert Faris (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2002)
An important part of Bolivia's fiscal revenues are directly tied to world oil prices. Since oil prices are very volatile, so are Bolivia's fiscal revenues. For example, if oil prices vary as much during the next couple of decades as they did during the previous two decades, then the fiscal revenues arising from our exports of natural gas to Brazil would vary between US 141 million per year and US 1.1 billion per year, and the revenues in any particular year would be largely unpredictable. Such volatility of fiscal revenues is undesirable, especially for a country that tries to implement a poverty reduction strategy requiring a steady and predictable flow of funds. This paper calculates the likely range values for the revenues that Bolivia will derive from natural gas exports, as well as the likely variation from year to year. Based on these calculations we design a Stabilization Fund, which accumulates money when world oil prices are high and distributes money when oil prices are low. The effect of oil price volatility on the Bolivian economy is evaluated in a CGE model and the advantages and disadvantages of a Stabilization Fund are analyzed.
Keywords: 330; Erdgas; Export; Ölpreis; Volatilität; Exporterlös; Bolivien